2018
DOI: 10.1097/md.0000000000009826
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and temporal dynamics of human immunodeficiency virus type 1 CRF01_AE and CRF07_BC among recently infected antiretroviral therapy-naïve men who have sex with men in Jiangsu province, China, 2012 to 2015

Abstract: The prevalence and incidence of human immunodeficiency virus type 1 (HIV-1) among men who have sex with men (MSM) are on the rise throughout China. With a large population of MSM, Jiangsu Province is facing an escalating HIV-1 epidemic.The aim of this study was to explore the phylogenetic and temporal dynamics of HIV-1 CRF01_AE and CRF07_BC among antiretroviral therapy (ART)-naïve MSM recently infected with HIV-1 in Jiangsu Province.We recruited MSM in Jiangsu Province (Suzhou, Wuxi, Nantong, Taizhou and Yanch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
5
8
0
Order By: Relevance
“…Our analyses dated the first introduction of HIV‐1 CRF07_BC into Nanjing in 1998 from IDU and to MSMs and HEs. The second epidemic wave was introduced into Nanjing in 2001 from MSM, which was consistent with previous studies 32,33 . Our results indicated that CRF07_BC in Nanjing likely originated from similar strains previously found among IDUs in Yunnan province.…”
Section: Discussionsupporting
confidence: 91%
“…Our analyses dated the first introduction of HIV‐1 CRF07_BC into Nanjing in 1998 from IDU and to MSMs and HEs. The second epidemic wave was introduced into Nanjing in 2001 from MSM, which was consistent with previous studies 32,33 . Our results indicated that CRF07_BC in Nanjing likely originated from similar strains previously found among IDUs in Yunnan province.…”
Section: Discussionsupporting
confidence: 91%
“…Our study found a total of 11 HIV-1 genotypes and 10 HIV-1 strains of URFs in 317 newly diagnosed HIV/AIDS patients in 2017, indicating that the distribution of HIV-1 genotypes in Shanghai is diverse and complex. The results were similar to that of the study conducted in Jiangsu province (a close neighbor of Shanghai), showing that the prevalence of genotype CRF01_AE, CRF07_BC, and B were 60.06, 22.29, and 5.88%, respectively [13]. Similarly, the surveys carried out in Hebei, Fujian, and regions across China also reported that CRF01_AE, CRF07_BC, and B were the predominant subtypes [9, 14, 15].…”
Section: Discussionsupporting
confidence: 80%
“…From 2006 to 2012 in Shenzhen, the prevalence of HIV-1 subtype B decreased from 37.5% to 5.7% and that of CRF01_AE decreased from 50.0% to 32.3%; however, the prevalence of CRF07_BC increased from 12.5% to 43.2% and that of CRF55_01B increased from 0% to 16.0% [25]. Between 2012 and 2015 in Jiangsu province, the prevalence of HIV-1 subtype CRF01_AE decreased from 56.5% to 49.3%, and that of CRF07_BC increased from 13.0% to 39.4% [26]. In the span of a few years, the prevalence of multiple HIV-1 subtypes have changed considerably.…”
Section: Introductionmentioning
confidence: 99%